House of cards. The complete fifth season [videorecording (DVD)] - Spacey, Kevin; Wright, Robin, 1966-; Kelly, Michael, 1969-; Clarkson, Patricia; Campbell, Neve, 1973-; Dobbs, Michael, 1948- (Sony Pictures Home Entertainment, 2017)
In the midst of the presidential election, tensions mount in the White House as Frank and Claire continue to navigate their political careers and redefine their relationships, particularly with each other.